Zustandsbestimmung von externen Spanngliedern und Schrägseilen mit Frequenzanalysen - Siegel, Steffen (Karlsruher Reihe Massivbau, Baustofftechnologie, Materialprüfung / Institut für Massivbau und Baustofftechnologie ; Materialprüfungs- und Forschungsanstalt Karlsruhe, 2018)
In this work, the measurement system ResoCable®, consisting of hardware and software, was developed with the implementation and evaluation of the frequency measurements of external tendons and cables. Numerous measurements at external tendons and cables were conducted. Among them, the behavior of strands and deflection points was investigated with FE calculations.